Circular economy and technological innovation : the regional implications - Khan, Syed Abdul Rehman, 1987-; Sheikh, Adnan Ahmed; Kolade, Oluwaseun; Kamble, Sachin (Industrial ecology, 2025)
This book explores the circular economy, its context, methodology, and commercial strategies, with a focus on waste minimization, recycling, green marketing, and sustainable business practices to facilitate resource recovery. It considers IR 4.0 and 5.0 to show how smart technology innovation extends circular economy through industrial organizational sustainability and investigates circular economy technology innovation in multiple scenarios to exploit product re-usability and technological innovation in Asian, European, and Australian contexts. It discusses novel digital technologies such as blockchain, additive manufacturing, AI, ML, and IoT for global supply chain tracking. This book is valuable for instructors and students in business, environmental studies, supply chain management, product re-manufacturing, and marketing programs seeking cutting-edge Circular Economy and Technological Innovation trends.